2016
DOI: 10.1111/eth.12529
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Isolation on Stress Responses to Novel Stimuli in Subadult Chickens (Gallus gallus)

Abstract: Extensive research has examined the effects of social isolation in neonatal and adult animal populations, but few studies have examined the effect of social isolation in early adulthood. Animals reaching reproductive age often experience extensive social changes as they leave their natal site, and a social stressor like isolation may uniquely affect this age group. Furthermore, adolescence is a time when sex differences in behavior become more pronounced. As such, the effects of social stressors are likely to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
2
4
0
Order By: Relevance
“…However, this effect was mainly driven by the HC-E, indicating that enrichment actually increased the sensitivity to social isolation. Socially isolating young chicks is well known to elicit a stress-response [44][45][46][47][48], and our results are…”
Section: Discussionsupporting
confidence: 72%
“…However, this effect was mainly driven by the HC-E, indicating that enrichment actually increased the sensitivity to social isolation. Socially isolating young chicks is well known to elicit a stress-response [44][45][46][47][48], and our results are…”
Section: Discussionsupporting
confidence: 72%
“…Movement in a novel environment likely entails a trade-off between motivation to reinstate social contact, motivation to explore the environment and motivation to avoid detection by potential predators 51 . In a previous study on domestic young chicks, it was concluded that young female chicks have a higher motivation for social reinstatement than males in a novel environment 52 , and a short latency to leave a start box has previously been linked to stress in chickens 51 . This in turn suggests that a short latency to move for our young female chicks most likely reflects a high motivation for social reinstatement.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, 99% of breeders experience isolation stress for more than 2 weeks. It has been suggested that the severity of isolation stress is higher for females than males and that multiple periods of 2‐week long isolation events dampen the stress response over time (Weldon et al., 2016 ). The reason for sex‐dependent severity of isolation stress is the natural dispersal pattern in males.…”
Section: Assessmentmentioning
confidence: 99%